2005
DOI: 10.1109/tuffc.2005.1561621
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of despeckle filtering in ultrasound imaging of the carotid artery

Abstract: It is well-known that speckle is a multiplicative noise that degrades the visual evaluation in ultrasound imaging. The recent advancements in ultrasound instrumentation and portable ultrasound devices necessitate the need of more robust despeckling techniques for enhanced ultrasound medical imaging for both routine clinical practice and teleconsultation. The objective of this work was to carry out a comparative evaluation of despeckle filtering based on texture analysis, image quality evaluation metrics, and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
239
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(252 citation statements)
references
References 48 publications
(183 reference statements)
2
239
0
8
Order By: Relevance
“…The segmentations were based on the Williams & Shah [37] snake segmentation method, which was used to deform the snake and segment the IMC, the atherosclerotic carotid plaque and the near carotid wall borders in each image. The snake v(s), adapts itself by a dynamic process that minimizes an energy function ( ( , ) snake E v s ) defined as [37] : [7,13,[15][16][17][18] .…”
Section: Imc Plaque and Diameter Snakes Segmentationmentioning
confidence: 99%
See 2 more Smart Citations
“…The segmentations were based on the Williams & Shah [37] snake segmentation method, which was used to deform the snake and segment the IMC, the atherosclerotic carotid plaque and the near carotid wall borders in each image. The snake v(s), adapts itself by a dynamic process that minimizes an energy function ( ( , ) snake E v s ) defined as [37] : [7,13,[15][16][17][18] .…”
Section: Imc Plaque and Diameter Snakes Segmentationmentioning
confidence: 99%
“…Recently, a sional (2D) ultr f a segmentati J IMT. With thi y detecting the h walls (far an re and diagnos ker of atherosc carotid lumen p of the IMT, th mperative and a easurements ar or semi-autom ntation and incr complex (IMC) the artery lume e far and near with 82% lum roposed in the l or the mediastudies reported ore specifically le in a more rec MC snake's ba ended for segm [17][18][19][20] and speck manually segm atherosclerotic MT snakes seg multi resolutio ks [25] with activ were utilized fferent 3D plaq sing the QLAB r the segmentat system for the rasound image ion system as p Journal of Biome is understandin leading echo b nd near wall) o se the extend o clerosis [4,5] . It diameter (D) ( he atherosclero are routinely as re performed m mated (SA) seg rease the accur ) (bands Z5 and en diameter, D walls on the men stenosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…& Step 2: Speckle reduction. Speckle noise is attenuated using a first-order local statistics filter (called lsmv by the authors [12,13]), which has given the best performance in the specific case of carotid imaging. This filter is defined by the following equation:…”
Section: Stage I: Far Adventitia Estimationmentioning
confidence: 99%
“…The noise-free central pixel in the moving window is indicated by J x,y . Louizou et al [12,13] mathematically defined k x;y ¼ s 2…”
Section: Stage I: Far Adventitia Estimationmentioning
confidence: 99%